2012
DOI: 10.3389/fpsyg.2012.00157
|View full text |Cite
|
Sign up to set email alerts
|

Response bias modulates the speech motor system during syllable discrimination

Abstract: Recent evidence suggests that the speech motor system may play a significant role in speech perception. Repetitive transcranial magnetic stimulation (TMS) applied to a speech region of premotor cortex impaired syllable identification, while stimulation of motor areas for different articulators selectively facilitated identification of phonemes relying on those articulators. However, in these experiments performance was not corrected for response bias. It is not currently known how response bias modulates activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 68 publications
8
50
0
Order By: Relevance
“…Our data demonstrate that, independent of its membership in the dorsal or ventral streams, the IPL is being exclusively recruited into the large-scale functional network controlling speech production but not the resting state. Furthermore, we show that the IPL recruitment is bilateral, as opposed to the proposed left lateralized contribution to the dual-stream model of speech control (Hickok and Poeppel 2007), but similar to the results of recent studies reporting a bilateral involvement of this region in different aspects of speech processing, such as phonological processing (Deschamps et al 2014;Hartwigsen et al 2010), speech-sound discrimination (Venezia et al 2012), silent speech reading (Chu et al 2013), and sensorimotor transformations during overt speech production (Cogan et al 2014). As we have reported earlier, the functional connectivity of the IPL with the LMC may be gradually increasing with the increased complexity of sound production ).…”
Section: Discussionsupporting
confidence: 85%
“…Our data demonstrate that, independent of its membership in the dorsal or ventral streams, the IPL is being exclusively recruited into the large-scale functional network controlling speech production but not the resting state. Furthermore, we show that the IPL recruitment is bilateral, as opposed to the proposed left lateralized contribution to the dual-stream model of speech control (Hickok and Poeppel 2007), but similar to the results of recent studies reporting a bilateral involvement of this region in different aspects of speech processing, such as phonological processing (Deschamps et al 2014;Hartwigsen et al 2010), speech-sound discrimination (Venezia et al 2012), silent speech reading (Chu et al 2013), and sensorimotor transformations during overt speech production (Cogan et al 2014). As we have reported earlier, the functional connectivity of the IPL with the LMC may be gradually increasing with the increased complexity of sound production ).…”
Section: Discussionsupporting
confidence: 85%
“…that requires disambiguation) (Rodd et al, 2005). A recent study has shown that response bias can modulate the speech motor system during speech processing (Venezia et al, 2012). Our findings in the left IFG are unlikely to be driven by response bias, however, because the present 2-alternative forced-choice task was unlikely to become systematically biased (i.e., participants had to choose one of two words on each trial, and the pairs of words differed from trial to trial).…”
Section: Regions Negatively Correlated With Snr (Or Positively With Nmentioning
confidence: 58%
“…Because categorical speech perception requires the listener to maintain sublexical representations in an active state as a metalinguistic judgment is made, it involves some degree of executive control and working memory functions (1). Thus, the linearly prolonged RT and incremental BOLD activity in the PMv, IFG, pSTG, and IPL with increasing task difficulty likely reflect an accumulation of effort-related changes in selective attention (33), phonological working memory (20,(26)(27)(28), or phoneme-category judgment and response selection (5,8,34).…”
Section: Discussionmentioning
confidence: 99%